Mechanism of Filling The Position of High Madya Leadership through The Office Auction System According to Law No. 5 Of 2014 Concerning The State Civil Apparatus - Songga Aurora (Epistemik Press, 2020)
Posisiton action system is one of the most effective strategies to fight nepotism, collusion and corruption in government positions. Filling positions in government is closely related to the rights of every person, which is the responsibility of political rights as part of human rights that must be guaranteed and protected by the State. The state should provide equal opportunities to every citizen to fill available positions in the government, including the position of regional secretary which is realized through the filling mechanism. This paper reviews the mechanism for filling middle high leadership positions through a job auction system using the concept of Good Governance which is carried out with a qualitative research approach.